The Transformation of Consumer Law in the EU in the Last 20 Years. Issue 3 (September 2013) - Stuyck, Jules
In the early years consumer protection was an exception to the logic of the internal market. Since the case of Dassonville in 1974, the CJEU has recognized the power of Member States to restrict free movement by reasonable measures in the interest of consumers (see in particular Cassis de Dijon in 1979). Harmonization of consumer laws will enhance the confidence of consumers and businesses and hence contribute to the internal market programme. So far, fundamental rights have played a limited role in EU consumer law. The contribution of EU consumer law to innovative governance is more important. There is an increasing number of regulations that directly set contractual rights for consumers, and alternative dispute resolution has gained momentum with the recent adoption of an ADR directive and an ODR regulation. The most significant evolution of consumer law in the past 20 years is innovation in the field of enforcement, both by the judiciary and the legislature, such as the active role of the judge (case law on the unfair contract terms directive), ADR, administrative cooperation and individual and collective remedies.